Examining the effects of punishment schedule density on the development and maintenance of avoidance and safety behaviours: Implications for exposure therapies. (December 2018) - Angelakis, Ioannis; Lewis, Venessa; Austin, Jennifer L.; Panagioti, Maria
Abstract: Background and objectives: Engaging in safety behaviors in the absence of actual threat is a key feature of many psychological disorders, including OCD and depression. Failure to discriminate between threatening and safe environments may make these behaviors resistant to change. The purpose of the current study is to investigate the conditions under which avoidance and safety behaviors are developed and maintained. Methods: In experiment 1, sixty-seven participants who were initially screened for low obsessive-compulsive behavior were invited to play a computerized game to gain points and avoid their potential loss. In Phase 1, they were exposed to a lean punishment schedule (relatively frequent point losses) and a dense schedule (highly frequent point losses). In Phase 2, they were tested on engagement in safety behaviors, where no punishment had been programmed. In experiment 2, twenty-two new participants were exposed to the lean punishment schedule followed immediately by the no point loss condition (Phase 2), one and two weeks after their initial exposure to the punishment conditions to test for the maintenance of safety behavior over time. Results: Findings demonstrated that participants developed avoidance immediately, but safety behavior was developed and maintained only for those who were exposed to the lean punishment schedule. Limitations: Prolonged exposure to dense punishment schedules may yield different results because the contrast between safe and aversive environments may be less discernible. Conclusions: These findings are important because they provide experimental evidence on the conditions that render safety behaviors difficult to amend, and offer important recommendations for clinical practice. Highlights: Avoidance was developed immediately under all punishment schedules (lean, dense). Safety behavior was only developed and maintained under the lean schedules. Immediate elimination of safety behavior may result in greater treatment resistance. When possible, use of safety behaviors should match the proportion of actual threat. Repeated short exposures to threat may be more beneficial than single longer ones.